Effect of the Kanghuier Transparent Hydrocolloid Dressing in Preventing Central Venous Catheter Infection and Phlebitis after Cardiac Surgery. (1st April 2022) - Han, Xiaoling; Li, Jiayi; Zeng, Ping; Luo, Chunfeng; Zhou, Dongmei
Abstract : Background . As cardiac surgery is complicated, time-consuming, and traumatic, it may cause great damage to the patient's body. Therefore, postoperative indwelling venous catheters are required for hemodynamic monitoring and rapid fluid replenishment. Intravenous catheterization infection can easily lead to phlebitis, which not only affects the success of the operation and patient recovery but may also lead to death in severe cases. Good perioperative care is key to reducing postoperative infection in patients, and the choice of dressings for patients with catheterization plays an important role in reducing catheter infection. Objective . The Kanghuier transparent hydrocolloid dressing is known to effectively prevent and treat wound infections. This study is aimed at exploring whether it can reduce the incidence of postoperative catheter infection and phlebitis in patients undergoing cardiac surgery. Methods . A total of 196 patients undergoing cardiac surgery in the Department of Cardiothoracic Surgery of Zhuhai People's Hospital (Zhuhai Hospital Affiliated with Jinan University) from January 2020 to June 2020 were selected. Among them, 98 patients receiving Kanghuier transparent dressing intervention were selected as group A, and the remaining 98 patients receiving traditional sterile gauze intervention were selected as group B. The incidence of infection and related complications, phlebitis, inflammatory factors, pain at the infusion site, nursing comfort and satisfaction, and quality of life were analyzed and compared between the two groups. Results . It was found that compared with group B, the postoperative central venous catheter infection rate and the incidence of phlebitis were significantly lower in group A. In addition, the inflammatory response of patients in group A was better relieved. Moreover, the nursing comfort and satisfaction and the quality of life of patients in group A were significantly improved. Conclusion . This study suggests that the Kanghuier transparent hydrocolloid dressing is effective in the prevention and treatment of central venous catheter infection and phlebitis in patients after heart surgery.